Marketing Innovation, Digital Marketing and Competitive Advantage as Determination of MSMEs Performance - Nuvriasari, Audita; As’ari, Hasim; Fauzan Rozi, Anief (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Small and medium-sized enterprises (MSMEs) have significant potential to enhance the well-being of individuals by reducing poverty, promoting income equality, and serving as a source of foreign exchange for the nation. Despite their significance, MSMEs commonly encounter challenges like innovation, technology utilization, and competition while building their business, all of which can influence their performance. This study aims to investigate how marketing innovation, digital marketing, and competitive advantage influence MSMEs performance in Yogyakarta. The study targets MSMEs owners and managers involved in marketing and business operations, with a sample size of 456 to ensure representative and valid results. To test the hypotheses, the researchers used SmartPLS version 4. The findings reveal a significant relationship between competitive advantage and MSMEs business performance. Digital marketing also shows a significant effect on business performance. Conversely, marketing innovation does not significantly impact MSMEs performance.